2001
DOI: 10.1176/appi.ajp.158.10.1631
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Sertraline Treatment and Serotonin Transport in Breast-Feeding Mother-Infant Pairs

Abstract: The data indicate that while mothers receiving clinical doses of sertraline experience substantial blockade of the platelet 5-HT transporter, platelet 5-HT uptake in nursing infants of treated mothers is unaltered. The observations suggest that mothers taking sertraline can breast-feed without appreciably affecting peripheral or central 5-HT transport in their infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
57
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(62 citation statements)
references
References 55 publications
4
57
0
1
Order By: Relevance
“…The usual absence of a discernible effect on infant platelet serotonin transport is consistent with the relatively low levels of sertraline in infant plasma [38].…”
Section: Sertralinesupporting
confidence: 61%
“…The usual absence of a discernible effect on infant platelet serotonin transport is consistent with the relatively low levels of sertraline in infant plasma [38].…”
Section: Sertralinesupporting
confidence: 61%
“…The impact of central serotonin 5-HT modulation by SSRI during critical periods of brain development is unknown. Although preclinical studies indicate that 5-HT plays important roles in neurogenesis and neural growth (14 -20), it is unclear how transporter inhibition affects early neurodevelopment in humans.Research on fetal and neonatal exposure to SSRI has been recently reviewed (10,11,21,22). Although substantial and physiologically meaningful infant SSRI exposure through breast-feeding by mothers receiving SSRI is probably infre- 0031-3998/04/5603-0418 PEDIATRIC RESEARCH Vol.…”
mentioning
confidence: 99%
“…Research on fetal and neonatal exposure to SSRI has been recently reviewed (10,11,21,22). Although substantial and physiologically meaningful infant SSRI exposure through breast-feeding by mothers receiving SSRI is probably infre- 0031-3998/04/5603-0418 PEDIATRIC RESEARCH Vol.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Others found undetectable levels in serum or levels of sertraline and its active metabolite desmethylsertraline of less than 10 ng/ml . Epperson et al (2001) studied serotonin (5-HT) transport in nine pairs of mothers and infants and concluded that at clinical doses of sertraline, platelet 5-HT uptake in nursing infants was unaltered and mothers taking sertraline could breast-feed without appreciably affecting peripheral or central 5-HT transport in their infants.…”
Section: Sertralinementioning
confidence: 99%